Improved athletic performance in highly trained cyclists after interval training - Lindsay, F. H.; Hawley, J. A.; Myburgh, K. H.; Schomer, H. H.; Noakes, T. D.; Dennis, S. C. (Medicine & Science in Sports & Exercise, 1996)
Trained cyclists (N = 8) who had a moderate degree of base training were subjected to four weeks of high-intensity interval training to see if simulated 40 km time trial performances could be improved. High-intensity interval training consisted of six to eight 5-min repetitions at 80% of peak power output. The recovery interval consisted of one minute pedaling at a low intensity. The interval training experience increased peak power output and fatigue resistance as well as improving simulated 40 km time trial performances. Implication: Performances improve if performance quality is increased on a daily basis over less-than-performance-specific base training. It is likely that the rate of improvement will be relatively quick but such improvements should not be expected to occur continually over longer durations.